Implementation of Cucumber Juice Administration to The Elderly for Reducing Blood Pressure in Hypertension Patients in Dusun IX, Tembung Village, Deli Serdang Regency: Penerapan Pemberian Jus Mentimun Bagi Lansia untuk Menurunkan Tekanan Darah pada Pasien Hipertensi di Dusun IX Desa Tembung Kabupaten Deli Serdang - Lusia Simatupang, Lenny; Mustikani Saragih, Dewi; Dama Yanti Harahap, Sri; Banjarnahor, Seriga; Marintan Sinaga, Regina (Universitas Haji Sumatera Utara, 2025)
Background: Hypertension is a chronic disease that requires a healthy lifestyle to prevent complications. One of the health problems that often occur in the elderly is experiencing a decline in body function due to physical, psychosocial, cultural, spiritual changes. Health problems that occur from the aging process are degenerative processes, including hypertension. Non-pharmacological treatment is needed to lower blood pressure such as giving cucumber juice. Giving cucumber juice is effective in lowering hypertension in the elderly because the high content of potassium, magnesium, and water in cucumbers helps regulate blood pressure, and is a natural diuretic that helps reduce excess fluid and reduce the workload of the heart. Objective: To determine the application of giving cucumber juice to the elderly to lower blood pressure in hypertensive patients. Method: Providing education to the elderly who have hypertension about the importance of consuming cucumber juice, conducting a demonstration of giving cucumber juice. Results: Based on the results above, it can be concluded that before being given interventions in the form of health education and demonstrations there were 7 people (35%) in the good category, 5 people (25%) in the sufficient category and 8 people (40%) in the less category and after being given interventions there was health education in the application of giving cucumber juice to the elderly to lower blood pressure in the Tembung village community, especially in Hamlet IX. There were 15 people (75%) in the good category, 3 people (15%) in the sufficient category and 2 people (10%) in the less category. Conclusion: There is an effect of education and demonstration of giving cucumber juice to the elderly on the level of knowledge of the elderly with hypertension in hamlet IX, Tembung village, Deli Serdang Regency. It is recommended for all elderly people to consume cucumber juice to reduce blood pressure.